Un gobernante de cinco k’atunes en Toniná, Chiapas - Alejandro Sheseña; Ángel A. Sánchez Gamboa; Guido Krempel; Alejandro Tovalín Ahumada (Journal de la Société des Américanistes)
In the present work, a recently found monument fragment from Toniná is analyzed. Notwithstanding the brief glyphic text, the fragment provides valuable information about one of the least known moments in the history of this city. Among other topics, the duration of the reign of the so-called “Ruler 8” is re-assessed and in turn allows us to specify part of the dynastic sequence of Toniná towards its last years of splendor.